PENGEMBANGAN MEDIA PEMBELAJARAN E-MODUL DENGAN MODEL PROJECT BASED LEARNING BERBASIS STEM SEBAGAI SUPLEMEN PEMBELAJARAN FISIKA PADA MATERI GERAK PARABOLA - Urmila, Khalida Putri; Perdana, Riki (Universitas Tanjungpura, 2023)
Nowadays education is in industry 4.0 where technology continues to develop over time. The development of this technology is very influential in various aspects, one of which is the way a teacher conveys learning. Emodule is a modification of conventional modules by combining information technology, so that it can display an interesting and interactive module. The aim of this research is to develop emodule learning media with a Project Based Learning model to improve learning concepts in parabolic motion material that is integrated with science, technology, engineering and mathematics, so that students do not only focus on the material. The method used in this research is the 4D development research method (Design, Develop, Dissaminate). This research was carried out by distributing validation sheets to experts in the field of physics education to determine the feasibility of the emodule developed from four aspects, namely material aspects, illustrations, media quality and appearance, and attractiveness. Then, data processing is carried out based on criteria on a scale of 5. The overall average value is based on 4 aspects